The impact of the complete atrioventricular block on in-hospital and long-term mortality in patients treated with primary percutaneous coronary intervention - Savić, Lidija; Mrdovic, Igor; Ašanin, Milika; Stanković, Sanja; Krljanac, Gordana (Vojnosanitetski pregled, 2023)
Background/Aim. The prognostic impact of complete atrioventricular (AV) block on the long-term prognosis of patients with ST-elevation myocardial infarction (STEMI) has not been fully determined. The aim of the study was to analyze the incidence and prognostic impact of complete AV block on in-hospital mortality (IHM) and 6-year mortality in STEMI patients treated with primary percutaneous coronary intervention. Methods. The study included 3,044 consecutive STEMI patients. Results. Complete AV block was registered only on admission in 144 (4.73%) patients; 125 (86.8%) patients with complete AV block had inferior infarction. A temporary pacemaker was implanted in 72 (50%) patients with complete AV block. No patient underwent permanent pacemaker implantation. IHM was significantly higher in patients with complete AV block than in patients without complete AV block: 17.9% vs. 3.6%, respectively, p < 0.001. In patients with heart block and inferior infarction, IHM was 13%, whereas IHM was 53% in patients with heart block and anterior infarction. When we analyzed patients discharged alive from the hospital, we also found a significantly higher long-term (6-year) mortality rate in those with complete AV block vs. patients without AV block: 7.8% vs. 3.4%, respectively, p < 0.001. Complete AV block was an independent predictor for IHM and 6-year mortality: IHM [odds ratio (OR) 2.94 95%, confidence interval (CI) 1.23–5.22; 6-year mortality hazard ratio (HR) 1.61, 95%, CI 1.10–2.37]. When subanalysis was performed in patients with inferior STEMI, complete AV block was an independent predictor of IHM and 6-year mortality, while in patients with anterior STEMI, complete AV block was an independent predictor of IHM. Conclusion. In analyzed STEMI patients, complete AV block was transitory and was registered only on hospital admission. Although transitory, complete AV block remained a strong independent predictor of IHM and long-term mortality.
Keywords: atrioventricular block; mortality; percutaneous coronary intervention; prognosis; st elevation myocardial infarction